1H MR spectroscopy in cervical carcinoma using external phase array body coil at 3.0 Tesla: Prediction of poor prognostic human papillomavirus genotypes. Issue 3 (19th July 2016) - Lin, Gigin; Lai, Chyong‐Huey; Tsai, Shang‐Yueh; Lin, Yu‐Chun; Huang, Yu‐Ting; Wu, Ren‐Chin; Yang, Lan‐Yan; Lu, Hsin‐Ying; Chao, Angel; Wang, Chiun‐Chieh; Ng, Koon‐Kwan; Ng, Shu‐Hang; et al.
Abstract : Purpose: To assess the clinical value of proton ( 1 H) MR spectroscopy in cervical carcinomas, in the prediction of poor prognostic human papillomavirus (HPV) genotypes as well as persistent disease following concurrent chemoradiotherapy (CCRT). Materials and Methods: 1 H MR spectroscopy using external phase array coil was performed in 52 consecutive cervical cancer patients at 3 Tesla (T). Poor prognostic HPV genotypes (alpha‐7 species or absence of HPV infection) and persistent cervical carcinoma after CCRT were recorded. Statistical significance was calculated with the Mann‐Whitney two‐sided nonparametric test and areas under the receiver operating characteristics curve (AUC) analysis. Results: A 4.3‐fold ( P = 0.032) increased level of methyl resonance at 0.9 ppm was found in the poor prognostic HPV genotypes, mainly attributed to the presence of HPV18, with a sensitivity of 75%, a specificity of 81%, and an AUC of 0.76. Poor prognostic HPV genotypes were more frequently observed in patients with adeno‐/adenosquamous carcinoma (Chi‐square, P < 0.0001). In prediction of the four patients with persistent disease after CCRT, elevated methyl resonance demonstrated a sensitivity of 100%, a specificity of 74%, and an AUC of 0.82. Conclusion: 1 H MR spectroscopy at 3T can be used to depict the elevated lipid resonance levels in cervical carcinomas, as well as help to predict the poor prognostic HPV genotypes and persistent disease following CCRT. Further large studies with longer follow up times are warranted to validate our initial findings. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:899–907.